IPO performance and trading around lock-up expiration - WANG, Yuchen (Institutional Knowledge at Singapore Management University, 2016)
During the lock-up period, company insiders are prohibited from selling their shares for a set period immediately after initial public offerings (IPOs), usually 180 days. This strict prohibition limits the borrowing of securities by short sellers within this period. Therefore, upon reaching the lock-up expiry date, the short-sale constraint may be loosened and new investors may rush into the stock market, which affects asset price and stock return. This thesis focuses on the IPOs’ performance during the lock-up period and the reasons for the unusual performance. The first section commences by questioning the role of the short seller and its relation to the stock return during the lock-up period. Since Regulation SHO required that short sale transaction data be made available during year 2005 to 2007, we are able to use the daily short selling transaction data to examine the trading behaviour of short sellers during the period around the lock-up expiry date. We find that transactions around the lock-up expiration are associated with a significant drop in the abnormal return. Furthermore, on the lock-up expiry day, the short selling percentage reaches the highest point, while stock return drops to the lowest level compared to the lock-up period. Hence, there is a connection between short sale and stock return on the lock-up expiry day. We then examine whether trading behaviour of short sellers around the lock-up expiration contains any information of future stock returns. The results all indicate a highly significant predictability of short seller trading activities on future stock returns. The findings lead us to develop the second section. Since there is a dramatic drop of IPOs’ abnormal return during the lockup expiry day in the Regulation SHO period, in the second section, we investigate whether this is a universal phenomenon by using a comprehensive sample period from year 1990 to 2014. By implementing an event study with a wider event window, we discover that the abnormal returns indeed decrease significantly during most of the sample period. However, we reveal that the return decline trend ceases right after the lock-up expiration and even reverses to the highest level of return before the lock-up expiry day for several years. Therefore, we may assume that the lock-up expiration event does not have a permanent impact on stock returns.